How Color Properties Can Be Used to Elicit Emotions in Video Games. (10th January 2016) - Geslin, Erik; Jégou, Laurent; Beaudoin, Danny
Abstract : Classifying the many types of video games is difficult, as their genres and supports are different, but they all have in common that they seek the commitment of the player through exciting emotions and challenges. Since the income of the video game industry exceeds that of the film industry, the field of inducting emotions through video games and virtual environments is attracting more attention. Our theory, widely supported by substantial literature, is that the chromatic stimuli intensity, brightness, and saturation of a video game environment produce an emotional effect on players. We have observed a correlation between the RGB additives color spaces, HSV, HSL, and HSI components of video game images, presented ton = 85 participants, and the emotional statements expressed in terms of arousal and valence, recovered in a subjective semantic questionnaire. Our results show a significant correlation between luminance, saturation, lightness, and the emotions of joy, sadness, fear, and serenity experienced by participants viewing 24 video game images. We also show strong correlations between the colorimetric diversity, saliency volume, and stimuli conspicuity and the emotions expressed by the players. These results allow us to propose video game environment development methods in the form of a circumplex model. It is aimed at game designers for developing emotional color scripting.